A legal perspective on gated communities in Malaysia - Sufian, Azlinor (International Islamic University Malaysia, 2006)

(untitled)
As a developing country, Malaysia is very much influenced by the concept of planning and housing development implemented in other countries. Although the “gated community” (GC) is already popular in other parts of the world; especially in developed countries for instance Florida, Arizona, Johannesburg, Pretoria, Lisbon, Madrid etc., this concept is relatively new to Malaysia. It has gained acceptance in Malaysia and attracted studies by professionals such as planners, designers, sociologists, criminologists, lawyers etc. who are keen to gain insights on its implementation as well as its significance to the development of the country, specifically in the cities. Discussion on GC is part of the prevalent features in built environment studies which has a direct link with the issue of creating a safer urban community. It is the aim of this paper to look into the legal aspects under the Malaysian law on the implementation of the GC concept involving landed properties such as bungalows and semi detached houses. This would involve considerations on the misconceptions of the GC concept by Malaysian housing developers and its legal consequences.